The 60 leading crops cultivated in Brazil, the economic value of pollination (EVP) of the harvest in 2019 and the degree of pollination dependence. Information on the degree of cropland dependence on pollinators are sourced from Klein et al. (2007), much of which are reiterated in Roubik (2018)1; Giannini et al. (2015)2; Campbell et al. (2018)3 and Dorneles et al. (2013)4. - Willams Oliveira (21442562) (2025)
The 60 leading crops cultivated in Brazil, the economic value of pollination (EVP) of the harvest in 2019 and the degree of pollination dependence. Information on the degree of cropland dependence on pollinators are sourced from Klein et al. (2007), much of which are reiterated in Roubik (2018)1; Giannini et al. (2015)2; Campbell et al. (2018)3 and Dorneles et al. (2013)4.